Rules for Sustainable Development to Protect Working Women in Iraqi Labor Law No. 37 of 2015 - Mahmood, Domoa; Rasheed, Saba (Journal of Legal Sciences, 2023)
Our research dealt with the issue of sustainable development related to the legal rules of the labor law in force to achieve the necessary protection for the rights of working women. The Iraqi labor law in force set several rules inspired by the texts of international conventions to protect working women at work. These rules were summarized in our research to the rules of protection from sexual harassment. At work, and the basis for obtaining decent work for women at work, Iraq was one of the countries organizing the Convention (CEDAW) that combats sexual harassment and gender discrimination, and which called for the importance of the presence of women in developing society and achieving the global goals of sustainable development. Development cannot be achieved without the participation of women On an equal footing with males, or if there is prejudice and discrimination between the sexes at work, the societies that respect women, pave the way for them, and provide them with the necessary protection to hone their skills and polish their ideas, are societies that are more developed and advanced than the rest of the societies that see women as just a person who comes after men and in their place Its mission is to serve the man and ensure his comfort.